The Effect Of Shared Reading Strategy on Students Reading Comprehension In Narrative Text at The Second Grade of SMPN 2 X Koto Tanah Datar In The Academic Year 2021/2022 - Isra Hayati; Genta Sakti; Veni Roza; Widya Safitri (Education : Jurnal Sosial Humaniora dan Pendidikan, 2022)
This study aims to determine the effect of the shared reading strategy on students' reading comprehension in class II narrative texts at SMPN 2 X Koto Tanah Datar for the 2021/2022 academic year. This research is caused by several problems related to teaching reading. First, students have difficulty identifying the main idea. Second, students lack the desire to read a text. The last is a problem related to teaching reading by the teacher. The strategy used in teaching reading is still conventional. To overcome this problem, researchers have implemented a shared reading strategy. This study uses experimental research. Researchers used a quasi-experimental design using a non-equivalent control group design. The population in this study were class II students at SMPN 2 X Koto. Sample in VIII. From the results of the calculation of the post-test values ​​of the two classes, the average post-test value (2) of the experimental class was 71.77. This is higher than the average post-test control class (1), 61.29. This means that the alternative hypothesis (Ha) is accepted and it can be interpreted that the reading test results of students who are taught using the shared reading strategy are better than the results of the reading tests of students who are not taught using the shared reading strategy. So, it can be concluded that all hypotheses are accepted. It is proven that the use of shared reading strategies helps students' reading comprehension of narrative texts well.